Coagulation testing in intracerebral hemorrhage related to non-vitamin K antagonist oral anticoagulants - Purrucker, Jan; Rizos, Timolaos; Wolf, Marcel; Khan, Shujah; Veltkamp, Roland (Neurocritical care, 2017)
BackgroundIntracerebral hemorrhage (ICH) is a life-threatening complication of non-vitamin K antagonist oral anticoagulants (NOAC). Little is known about the effect of intensity of anticoagulation on NOAC-ICH. We describe the current use of coagulation testing in the emergency setting and explore associations with baseline size and expansion of hematoma as determined in a previous study.MethodsData from the prospective multicenter RASUNOA registry were analyzed. Patients with NOAC-ICH were enrolled between February 2012 and December 2014. Frequency of local test performance of specific (anti-factor Xa tests, diluted thrombin time) and non-specific tests (international normalized ratio (INR), activated partial thromboplastin time (aPTT), thrombin time) was analyzed. The association of anticoagulation intensity at admission with hematoma volume and hematoma expansion was explored.ResultsIn 61 NOAC-ICH patients enrolled at 21 centers, drug-specific coagulation testing was performed in 16 cases (26%), and only 29% of centers appeared to use drug-specific tests in NOAC-ICH at all. In some cases, INR and aPTT values were normal despite drug concentrations in the peak range. In patients with available drug-specific concentrations, 50% had drug levels in the peak range at admission. Higher intensity of anticoagulation was not associated with higher hematoma volume at admission or with subsequent hematoma expansion.ConclusionDrug-specific tests are only infrequently used in NOAC-ICH. Normal results in non-specific coagulation do not reliably rule out peak range concentrations. Anticoagulation intensity at admission does not predict baseline hematoma volume or subsequent hematoma expansion.